PEMANFAATAN POTENSI WISATA DESA DAN BENDA CAGAR BUDAYA SEBAGAI OUT BOUND PEMBELAJARAN IPS DAN ECOTOURIME DI KABUPATEN BIMA - A. Gafar Hidayat; Tati haryati (Jurnal Terapung : Ilmu - Ilmu Sosial, 2024)
The village of Bumi Pajo has several attractions that can be developed as targets for outbound activities and ecotourism, such as cultural heritage sites (WaduTunti/Inscription sites), ancient graves, Oli Kaleli waterfall, fruit orchards, and its characteristic location in highlands/summits. Due to the presence of cultural heritage sites/objects, the village can be utilized as a location for outbound Social Studies learning. The objectives of this research are as follows: 1) Identifying and gathering all potential tourism attractions in Bumi Pajo village; 2) Describing and analyzing efforts to utilize sites and natural environments as outbound Social Studies learning resources; 3) Conceptualizing the village's tourism potential as ecotourism attractions. This research employs a qualitative method with a pure descriptive approach or survey research. Based on the research findings, the village's tourism potential has a positive impact on improving the welfare of local communities and preserving cultural heritage. Tourism potentials such as the Wadu Tunti inscription site, Oi Kaleli waterfall, and fruit orchards in Bumi Pajo village can be used as locations for outbound Social Studies learning and also tourist attractions, which can be managed and utilized for educational purposes, enhancing the welfare of local communities, especially in the economic sector. To optimize this potential, it is necessary to encourage active participation from the local community in managing and preserving the natural environment and cultural heritage sites